Oil and oil dispersant do not cause synergistic toxicity to fish embryos. (5th November 2013) - Adams, Julie; Sweezey, Michael; Hodson, Peter V.
Abstract Atlantic herring (Clupea harengus) embryos were exposed to water accommodated fractions (WAFs; oil dissolved in water) and chemically enhanced water accommodated fractions (CEWAFs; oil dispersed in water with Corexit 9500A) of Medium South American (MESA) crude oil. The CEWAF was approximately 100‐fold more toxic than WAF based on nominal loadings of test solutions (% v/v). In contrast, the ratio of WAF and CEWAF toxicity expressed as measured oil concentrations approximated 1.0, indicating that the higher toxicity of CEWAFs was caused by an increase in exposure to hydrocarbons with chemical dispersion. In a second experiment, the chronic toxicity of Corexit 9500A and chemically dispersed heavy fuel oil 7102 (HFO 7102) to rainbow trout (Oncorhynchus mykiss) embryos was compared to chemically dispersed Nujol, a nontoxic mineral oil. Dispersant alone was toxic, but caused different signs of toxicity than HFO 7102. Nujol at a dispersant‐to‐oil ratio of 1:20 was nontoxic, suggesting that dispersant was sequestered by oil and not present at toxic concentrations. In contrast, the same nominal loadings of dispersed HFO 7102 caused concentration‐dependent increases in toxicity. Both experiments suggest that chemically dispersed oil was more toxic to fish embryos than solutions created by mechanical mixing due to the increased exposure of fish to petroleum hydrocarbons and not to changes in hydrocarbon toxicity. The Nujol control discriminated between the toxicity of oil and chemical dispersant and would be a practical addition to programs of dispersant testing. Environ Toxicol Chem 2014;33:107–114. © 2013 SETAC